View-dependent 3-D mesh coding by rate allocation with the image rendering-based distortion measures. Issue 5 (July 2016) - Bayazit, Ulug; Alper, Muzaffer
Abstract Low-bandwidth transmission of synthetic digital content to the end user device in the form of a scene of 3-D meshes requires efficient compression of the mesh geometry. For applications in which the meshes are observed from a single viewpoint, this work explores the use of the image rendering-based distortion measures in rate allocation to their surface regions for view-dependent mesh geometry compression. It is experimentally demonstrated that the image rendering-based distortion measures yield far superior performance (the quality of the rendered image of the reconstructed scene from a viewpoint at a given rate) in optimal rate allocation than other previously proposed distortion measures. A fast rate allocation method is also proposed for use with the image rendering-based measures for real-time or interactive applications. Not only does this method have significantly lower complexity than the optimal rate allocation method due to the rendering of the images of the reconstructed meshes at only judiciously selected rate–distortion operating points, but also its coding performance is just as competitive. Further complexity reduction in rate allocation, through rendering of only the coded regions of the meshes, is also investigated.